1999
DOI: 10.1161/01.str.30.7.1402
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Predictors of Cerebral Vasospasm Occurrence After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-The role of type of treatment on cerebral vasospasm occurrence after aneurysmal subarachnoid hemorrhage (SAH) has not been studied. Through multivariate analysis we determined the independent prognostic factors of the occurrence of symptomatic vasospasm following aneurysmal SAH in a study cohort of 244 patients undergoing either surgical or endovascular treatment. The prognostic factors of sequelae after aneurysmal SAH were studied as well. Methods-Symptomatic vasospasm was defined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
152
9
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(177 citation statements)
references
References 47 publications
15
152
9
1
Order By: Relevance
“…The DCI occurs in approximately one third of aSAH patients, mostly between days 4 and 10 (Roos et al, 2000) and can progress to irreversible cerebral infarction with subsequent poor clinical outcome (Rosengart et al, 2007). Patients with hyperglycemia on admission or during the clinical course develop DCI and cerebral infarction more often than patients with normal blood glucose levels (Badjatia et al, 2005;Charpentier et al, 1999;Frontera et al, 2006;Juvela et al, 2005;Kruyt et al, 2008;Lanzino, 2005). The association between admission hyperglycemia and DCI was weaker than that of persistent hyperglycemia and DCI, and the association between admission glucose and DCI did not persist after multivariable assessment in several studies (Badjatia et al, 2005;Frontera et al, 2006;Juvela et al, 2005;Kruyt et al, 2008).…”
Section: How Does Hyperglycemia Affect Outcome After Aneurysmal Subarmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCI occurs in approximately one third of aSAH patients, mostly between days 4 and 10 (Roos et al, 2000) and can progress to irreversible cerebral infarction with subsequent poor clinical outcome (Rosengart et al, 2007). Patients with hyperglycemia on admission or during the clinical course develop DCI and cerebral infarction more often than patients with normal blood glucose levels (Badjatia et al, 2005;Charpentier et al, 1999;Frontera et al, 2006;Juvela et al, 2005;Kruyt et al, 2008;Lanzino, 2005). The association between admission hyperglycemia and DCI was weaker than that of persistent hyperglycemia and DCI, and the association between admission glucose and DCI did not persist after multivariable assessment in several studies (Badjatia et al, 2005;Frontera et al, 2006;Juvela et al, 2005;Kruyt et al, 2008).…”
Section: How Does Hyperglycemia Affect Outcome After Aneurysmal Subarmentioning
confidence: 99%
“…Besides neurologic complications, patients with aSAH often have cardiopulmonary and general medical complications that can influence outcome. Hyperglycemia in aSAH patients is common and associated with poor clinical outcome (Badjatia et al, 2005;Charpentier et al, 1999;Dorhout Mees et al, 2003;Frontera et al, 2006;Kruyt et al, 2008Kruyt et al, , 2009Lanzino et al, 1993). As treatment for hyperglycemia is available, it has attracted increasing attention as a target for intervention, although adequate and safe glycemic control is difficult to achieve in patients with aSAH.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the day of the hemorrhage as day 0, surgical intervals were defined either as immediate (day 0), early (days 1-3), intermediate (days [4][5][6][7][8][9][10][11][12][13][14] or late (days after 14).…”
mentioning
confidence: 99%
“…However, when patients with Fisher grade 4 and Hunt and Hess grade V lesions were excluded, the difference between the treatment groups was no longer significant. Other authors 19,34,35 have not found an increased risk of vasospasm with endovascular therapy as well. They concluded that the type of treatment was not associated with an increased risk of cerebral vasospasm.…”
Section: Ischemic Eventsmentioning
confidence: 88%